Strategy for nursing research in Sweden - Clara Aarts (Universidad de Antioquia, 2017)
Sweden has about 10 million inhabitants. The responsibility for health and medical care is shared by the central government, county councils (n=20) and municipalities (n=290).1 Health care in Sweden is largely tax-funded, a system that ensures equal access to health care services. Health and medical care represents about 7.5 percent of Sweden's gross domestic product (GDP). Sweden has 61 hospitals, seven are regional hospitals, and about 1200 Primary Health Care Centers, of which > 40% are private centers year 2015. It is common nowadays for county councils to buy services from private health care providers but patients are covered by the same regulations that apply to municipal care facilities. Research example at our Department, Associate Professor Ulrica Winblad and research group who study the effects of marketization on health care.